Стан і перспективи розвитку вуглезбагачення в Україні - Lyashenko O.F.; Perov M.O.; Novytskyi I.Yu. (General Energy Institute of the National Academy of Sciences of Ukraine, 2007)
The state is analyzed, tendencies and prospects of coal preparation development in Ukraine are determined on the comparative basis of some quantitative-quality parameters for the 1990-2005 period.